A stakeholder approach to issues management - Boutilier, Robert, 1950- (New York, N.Y. : Business Expert Press, 2012)
Offers a fact-based strategy development process for managing issues and controversies. The book shows practitioners how to ground their strategic advice on empirical research that reveals the socio-political dynamics of the issue. It is the first book to approach issues management from a blended application of advances in stakeholder theory and social network analysis. Readers learn how to track the socio-political environment in order to (a) avoid risks and crises, (b) obtain essential environmental scanning information for strategy development or adjustment, and (c) secure the organization's reputation and access to vital resources.
Includes bibliographical references (p. 145-167) and index.
Keywords: Customer relations; Issues management; Social networks